Landslide susceptibility in Rasuwa District of central Nepal after the 2015 Gorkha Earthquake - Pokharel, Badal; Thapa, Prem Bahadur (Journal of Nepal Geological Society, 2019)
The 2015 Gorkha Earthquake (7.8 Mw) triggered several landslides in central Nepal with major damages in 14 districts. Among them, the Rasuwa district at the north of Kathmandu Valley faced severe landslides due to rugged topography, complex geology and improper land use development. The landslides had blocked the Pasang Lhamu Highway and dammed the Trishuli River at many places. A total of 1416 landslide locations were detected in the district from high resolution satellite images in Google Earth. In this study, landslide susceptibility was modeled in the Rasuwa District by considering slope, aspect, elevation, geology, peak ground acceleration (PGA), land use, drainage proximity and thrust proximity as the predictive factors for landslide occurrences. The landslide inventory was split into 70% and 30% portions as the training dataset and testing dataset respectively. The results from modified frequency ratio (FR) suggest that effect of geology with prediction rate 2.52 is the highest among all factors and is followed by elevation (2.38) and drainage proximity (2.12). The results were verified using area under curve (AUC) and the prediction rate was found to be 79.14%. The computed landslide susceptibility map is helpful for land use planning and landslide risk reduction measure in the Rasuwa District.